Periodic Solutions of Second-Order Difference Problem with Potential Indefinite in Sign - Honghua Bin (Abstract and Applied Analysis)
We investigate the periodic solutions of second-order difference problem with potential indefinite in sign. We consider the compactness condition of variational functional and local linking at 0 by introducing new number . By using Morse theory, we obtain some new results concerning the existence of nontrivial periodic solution.